Optimal allocation of distributed generation for planning master–slave controlled microgrids - Pasha, Aisha M; Zeineldin, Hatem H; El-Saadany, Ehab F; Alkaabi, Sultan S (IET generation, transmission & distribution, 2019)
This study proposes a novel problem formulation for a planning distributed generation (DG) allocation for microgrids, using the master–slave approach. In the previous planning studies, all DGs have the same operating mode (e.g. operate at unity power factor). For master–slave controlled microgrid, DGs have two possible operating modes: master (non-unity power factor operation) and slave (unity power factor operation). For planning a master–slave controlled microgrid, in addition to DG siting, the optimal DG operating mode is determined by including a new set of constraints in the planning problem. Thus, the proposed formulation is capable of determining the optimal location of the master and slave DGs with the main objective of minimizing the microgrid's energy losses. The proposed model is formulated as a mixed-integer non-linear programming problem; incorporated into an optimal power flow framework and tested on the IEEE 38-bus systems considering a variable load profile. In addition to this, sensitivity analysis is carried for case studies with different load types and reactive power injection by the slave DGs in the system (e.g. operate at fixed non-unity power factor). The proposed approach can serve as an efficient tool for utility operators for planning microgrids.